The Effect of Leadership and Work Motivation on Operator Performance - Mohzana Mohzana; Muh Fahrurrozi; Hary Murcahyanto (STAI Hubbulwathan Duri, 2022)
Information technology in the education system today is very advanced and completely online, so the performance needs of school operators will determine the quality of schools in addition to the leadership and work motivation of the principal. This study aims to analyze the effect of leadership and work motivation on the performance of elementary school operators and analyze the influence of the principal's leadership on the work motivation of school operators. This study uses quantitative methods to examine three variables, namely two independent variables and one dependent variable. This research was conducted using quantitative research with a survey method with a correlational approach, with a total population of 26 principals and 26 school operators so the population was 52 people. The sample was carried out by the census method. The instrument test in this study used validity and reliability tests. Using descriptive analysis and hypothesis testing. The results of the calculation of normality in the principal's leadership data as the dependent variable (X1) the hypothesis is accepted in other words the data is normally distributed. In the work motivation data as the dependent variable (X2), the hypothesis is accepted in other words, the data is normally distributed. In the school operator's performance data as an independent variable (Y), the hypothesis is accepted in other words the data is normally distributed. In the linearity test, there is a linear relationship between the principal's leadership variable (X1) and the work motivation variable (X2) on the school operator's performance variable (Y). The conclusion of this study is that there is an influence of leadership on the performance of school operators, there is an influence of leadership on the performance of school operators and there is an influence of leadership and work motivation of the principal on the performance of school operators.